Visual Representations as Environing Technologies: Anticipating the Øresund Fixed Link in Danish and Swedish Printed Media (1930-1999) - Francesco ZAVATTI (Diacronie. Studi di Storia Contemporanea, 2022)
This article shows that visual representations are valuable sources for investigating the cultural and social history of the humankind-nature relationship. It does so by considering visual representations of future acts of environing as technologies that, connoting the making of the environment, disclose societal sensibilities and actors’ agendas regarding technology, the environment and nature. By analysing a series of visual representations of one yet-unrealised mobility infrastructure published in the Danish and Swedish printed media from 1930 to 1999, the article shows that technological utopias and warnings over the consequences of environing competed to connote visually the act of environing throughout the last century.